Study of Back-Channel Defect States on Bottom-Gate IGZO TFTs Using Capacitance-Voltage Analysis. Issue 1731 (23rd February 2015) - Mudgal, T.; Walsh, N.; Edwards, N.; Manley, R.G.; Hirschman, K.D.
ABSTRACT: This work investigates the quality of back-channel passivation applied to sputter-deposited IGZO bottom-gate TFTs. Passivation materials investigated were alumina, silicon dioxide, and B-staged bisbenzocyclobutene-based (BCB) resins. Sputtered quartz and PECVD (TEOS) SiO2 rendered the IGZO material highly conductive ( ρ < 0.01 Ω·cm), with subsequent annealing in oxidizing ambient unable to restore a high-resistivity state. Appropriate channel resistivity was restored on devices passivated with electron-beam evaporated alumina and spin-coated BCB when followed by annealing in air. Alumina passivated devices demonstrated improved stability; however slight distortions in measured I-V and C-V characteristics were observed. TCAD simulation was used to develop an IGZO material/device model, with results indicating the significant presence of oxygen-vacancy (OV) interface traps and negative fixed charge remaining at the back-channel.